Performance of synacthen test in chronic hemodialysis patients - Manuela Nickler; Susanne Stampf; Luca Bernasconi; Stephan Segerer; Claudine A. Blum; Min Jeong Kim (BMC Nephrology, 2023)
Abstract Background Adrenal function tests (Synacthen test) in chronic hemodialysis (HD) patients are currently performed off dialysis. The study aimed to demonstrate equivalence of serum cortisol concentrations pre- and during HD, each for standard-dose (250 µg) and low-dose (1 µg) Synacthen test. Methods In a single-center cross-over diagnostic equivalence study, Synacthen tests were performed in four settings, in standard- and low-dose as well as pre- and during HD. Serum cortisol concentration was measured at 30 and 60 min after Synacthen administration, and additionally at 20 min in low dose test. Based on a multivariable linear mixed model the means of cortisol concentration on log-scale were estimated in each dose and test time combination. Differences in means were calculated and the TOST approach was applied to test for equivalence. Equivalence was proven if the 90% confidence interval of the difference of two cortisol means was entirely between − 0.22 and 0.22. Results In 28 chronic HD patients, serum cortisol concentrations at 30 and 60 min after Synacthen administration in both standard- and low-dose were shown to be equivalent pre- and during HD. In 10 of 56 low-dose tests, the cortisol peak was already reached after 20 min. However, cortisol concentrations at 20 and 30 min after low-dose Synacthen test pre- and during HD showed no significant difference. Conclusion These results suggest that the adrenal function test may be carried out during an ongoing HD session, leading to a more patient-friendly performance of the test, less organizational effort and potentially earlier diagnosis of adrenal insufficiency.